Traits of vulnerability and poverty in female domestic workers in Zacatecas - Morales-Díaz, Zayra Yadira (2022)
The objective is to reveal the particular attributes of vulnerability and poverty currently reported by domestic workers (TDH) in Zacatecas; peculiarities related to their de facto working conditions and the status of informality that persist, despite the public attention received in recent years. The issue is approached from the feminist economic perspective, making visible a critical social problem and uncertainty that the devaluation of domestic work entails. The results obtained with the application of a survey and ten in-depth interviews show the relative prevalence of labor exclusion; lack of continuity with the same employer with permanence in the same occupation; deficient contractual terms with respect to the legal floor, which extend to the absence of social protection and employment instability, and in addition, violation of physical integrity and human dignity in the workplace. Likewise, the analysis of evidence suggests that the precariousness of this labor segment is not only the responsibility of the employers, but rather that it responds to a systemic framework that prevents TDHs from obtaining better employment conditions and, therefore, of life.